In algebra, the composition of functions refers to combining two functions such that the output of one function becomes the input of another function. If we have two functions, \(f(x)\) and \(g(x)\), the composition of \(f\) and \(g\) is written as:
\[(f β g)(x) = f(g(x)) \]
This is read as "\(f\) composed with \(g\) of \(x\)" or "\(f\) of \(g\) of \(x\)." In composition, the inner function g is applied first, and then the result is used as input into the outer function \( f\). This means you first apply \(g(x)\), then take the result and apply \(f\) to it.
Example 1: Basic Polynomial Functions
Let
Note: In general, \[(f β g)(x) β (g β f)(x)\]
Example 2: Real-World Interpretation
Let
Example 3: Value of composition
Let
While it's generally true that: \[(f β g)(x) ≠ (g β f)(x)\] there are special cases where \[(f β g)(x) = (g β f)(x)\]
Letβs explore some examples where they are equal
Note: Why? Because the identity function does nothingβit returns the input as-is. So composition with the identity function always preserves the other function.
Note: Why? Because when π = π, the order of composition doesnβt matterβyouβre applying the same function twice.
Why? Because addition is commutative: \[(x +1) + 2 = (x + 2) + 1 \]
Examples of Inverse Functions
Example 1
Let
$$ f(x) = 2x $$
$$ g(x) = x / 2 $$
Check the compositions:
$$ f(g(x)) = 2 * (x / 2) = x $$
$$ g(f(x)) = (2x) / 2 = x $$
Both compositions return \(x\).
Example 2:
Let
$$ f(x) = x + 3 $$
$$ g(x) = x - 3 $$
Check the compositions:
$$ f(g(x)) = (x - 3) + 3 = x $$
$$ g(f(x)) = (x + 3) - 3 = x $$
β
Again, both compositions return \(x\).
Example 3:
Let
$$ f(x) = 1/x $$
$$ g(x) = 1/x $$
(Note: f(x) is its own inverse here.)
Check the compositions:
$$ f(g(x)) = f(1/x) = 1 / (1/x) = x $$
$$ g(f(x)) = g(1/x) = 1 / (1/x) = x $$
β
Both return \(x\).
Summary:
General Conditions When \[(f β g)(x) = (g β f)(x) \]
For linear functions f(x) = ax + b, g(x) = cx + d, the compositions are equal if:
\[d(a - 1) = b(c - 1)\]
Proof:
let,
\[f(x) = ax +b\]
and
\[(x) = cx +d\]
To find when
\[(f β g)(x) = (g β f)(x) \]
Compute:
\[f(g(x))=f(cx+d)=a(cx+d)+b=acx+ad+b \]
Compute:
\[ g(f(x))=g(ax+b)=c(ax+b)+d=acx+bc+d \]
Set equal:
\[ acx+ad+b=acx+bc+d \]
Equating constants:
\[ad+b=bc+d\]
Solve for this:
\[adβd=bcβbβd(aβ1)=b(cβ1)\]
This equation must be true for πβπ=πβπ for linear functions.
Summary: